Let's Take the Pulse of the Classroom on Sustainability! An Exploratory Study on Student Views and Teacher Solution Suggestions Regarding Sustainable Development Goals - Efe, Hacer; Umdu Topsakal, Uensal (MDPI, 2025)
Sustainable development goals aim to build a sustainable and prosperous world for future generations. Education, one of the sustainable development goals, is also an important predictor of other development goals. The aim of this study is to analyze the views and suggestions of students and teachers on sustainable development goals. In this context, semi-structured interviews were conducted with 30 students and three teachers who participated in the study and the interview form prepared by the researchers as a data collection tool was analyzed with content analysis. As a result of the analysis, students' answers were concentrated on the themes of environmental pollution, social equality, renewable energy sources, natural habitats, and improvement of the economy regarding sustainable development goals; teachers' answers were concentrated on the themes of changes in curriculum and textbooks, in-school/outside-school activities, and collaborations that schools will establish with institutions. As a result of this study, it was concluded that students' views and teachers' solution suggestions regarding sustainable development goals were limited. Since this study is a qualitative study covering both students and teachers, it is expected to provide a good starting point in planning and developing educational strategies for sustainable development goals.
Keywords: sustainable development goals; exploratory study; students; teachers; views; solutions; classroom; EDUCATION; Science & Technology - Other Topics; Environmental Sciences & Ecology